Heamodynamics and Analgesic effects of Infusion in Day Care Laparoscopic Surgery - Hossain, Md Mozaffer (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Abstract not available J Bangladesh Coll Phys Surg 2024; 42: 303-304